MOTIVASI LATIHAN TIM BOLA VOLI PUTRI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BENGKALIS VOLI KLUB DALAM MENCAPAI PRESTASI DI BENGKALIS - Rahmadi, Catur Riga; Vai, Aref; Rusmanto, Rusmanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The purpose of this research is to determine the level of trainingmotivation for the women's volleyball team at the Public Works and Spatial PlanningService of Bengkalis Regency for club volleyball in achieving achievements inBengkalis. This research is descriptive research, namely research that provides anoverview of the research object as it is. The data analysis technique in this researchuses descriptive analysis techniques. From the results of the analysis, it can be seen thatthe training motivation of the Bengkalis Regency Public Works and Spatial PlanningService women's volleyball team for club volleyball in achieving achievements inBengkalis is quite good considering that the highest frequency is in the sufficientcategory with 7 people or 46.67%. The women's volleyball team of the Public Worksand Spatial Planning Department of Bengkalis Regency, club volleyball in achievingachievements in Bengkalis in the very good category, none, either 5 people or 33.33%,just 7 people or 46.67%, less than 2 people or 13, 33% and very less than 1 person or6.67%. This situation shows that the training motivation of the Bengkalis RegencyPublic Works and Spatial Planning Service women's volleyball team for club volleyballin achieving achievements in Bengkalis is quite good.Keywords: Training Motivation, Women's Volleyball Team